An alternative paradigm for assessing attitudes in virtual reality — Interpersonal distance paradigm: Taking weight stigma as an example - Gu, Xiang; Chen, Lihan; Wang, Guoping; Li , Sheng (Frontiers in Virtual Reality, 2022)
Immersive virtual technology has been widely used to modulate sociocognitive processes, such as changing individuals’ implicit attitudes towards specific groups. As to measure the effect, the implicit association test (IAT) is the most used one. However, IAT itself is controversial for its construct validity and commonly requires participants to quit virtual environments (VEs) to complete. Here, we propose an alternative paradigm, the ‘interpersonal distance paradigm’, which measures attitudes using interpersonal distance and can be conducted in VEs. We conducted a user study measuring weight stigma to compare the effectiveness of the interpersonal distance paradigm with two classical paradigms: the questionnaire and IAT. Results revealed a floor effect in the questionnaire method and no significant correlation between the two classic paradigms. The measurement of interpersonal distance showed a weak positive correlation with the questionnaire score, but not with IAT score. In future research, the results of more measurement methods should be combined to obtain more accurate results to better evaluate this new paradigm’s validity. The accurate results can help quantify the effects of the programs aiming at reducing weight stigma.